2018
DOI: 10.5897/ajb2018.16566
|View full text |Cite
|
Sign up to set email alerts
|

Chromium (III) and its effects on soil microbial activities and phytoremediation potentials of Arachis hypogea and Vigna unguiculata

Abstract: The aim of this research was to evaluate the impact of chromium (III) nitrate on soil microbial activities and growth performance and phytoremediation potentials of two staple leguminous crops, namely cowpea (Vigna unguiculata) and groundnut (Arachis hypogea). Pristine sandy loam soil samples were polluted with nitrate salts of chromium (III) at four different levels (50, 100, 200 and 400 mg/kg) in triplicates. There was a significant (P < 0.05) retarding effect of this metal on the study parameters. A consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…This delay in germination time suggests the possibility of secondary induced dormancy in response to metal concentrations [ 60 ]. These current findings are consistent with those of Eze et al [ 61 ], who similarly observed delayed germination in Cr-treated soils, with concentrations of up to 400 mg/kg compared to the control treatment, indicating that germination time increased with higher levels of metal contamination in soils.
Fig.
…”
Section: Resultssupporting
confidence: 93%
“…This delay in germination time suggests the possibility of secondary induced dormancy in response to metal concentrations [ 60 ]. These current findings are consistent with those of Eze et al [ 61 ], who similarly observed delayed germination in Cr-treated soils, with concentrations of up to 400 mg/kg compared to the control treatment, indicating that germination time increased with higher levels of metal contamination in soils.
Fig.
…”
Section: Resultssupporting
confidence: 93%
“…Thus, the higher pH and accumulation of Cr in soil under the highest rate of compost can contribute to decrease incorporation of C by microbes. Indeed, Cr presents an inhibitory effect on C incorporation by microbes and this effect is concentration-dependent [29]. On the other hand, soil pH is an important driver that affects the efficiency of accumulating C into microbial biomass [25].…”
Section: Resultsmentioning
confidence: 99%
“…Several soil properties influence the soil respiration, being moisture, temperature, and organic C content, which are the most important soil factors [23]. In particular, soil temperature and moisture are important factors influencing microbial activity acting on organic C [29,30]. The respiratory quotient also varied according to treatments over time (Figure 2D).…”
Section: Resultsmentioning
confidence: 99%
“…Of the species that were identified at Picacho and El Ensayo, the following 28 complied with the selection criteria and thus can be considered appropriate for multifunctional agroforestry/phytoremediation systems in Chinandega: Amaranthus Spinosus [31], Anacardium occidentale [32], Arachis hypogaea [33], Arachis pintoi [34], Azadirachta indica [35], Brachiaria ruziziensis [36], Byrsonima crassifolia [37], Ceiba pentandra [38], Chrysopogon zizanioides [38],…”
Section: Exploration Of Appropriate Phytoremediation Species For Chin...mentioning
confidence: 99%